2013
DOI: 10.1158/1078-0432.ccr-12-3276
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Plex Methylation Assay Combined with the FGFR3 Mutation Assay Sensitively Detects Recurrent Bladder Cancer in Voided Urine

Abstract: Purpose: DNA methylation is associated with bladder cancer and these modifications could serve as useful biomarkers. FGFR3 mutations are present in 60% to 70% of non-muscle invasive bladder cancer (NMIBC). Low-grade bladder cancer recurs in more than 50% of patients. The aim of this study is to determine the sensitivity and specificity of a urine assay for the diagnosis of recurrences in patients with a previous primary NMIBC G1/G2 by using cystoscopy as the reference standard.Experimental Design: We selected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 52 publications
0
51
1
1
Order By: Relevance
“…A 10-biomarker ELISA-based assay (IL8, MMP9, MMP10, SERPINA1, VEGFA, ANG, CA9, APOE, SDC1, and SERPINE1) provided an overall AUC of 0.85 (95% CI, 0.80-0.91) in discriminating urothelial bladder cancer patients from healthy and benign controls (45), slightly lower than the rates received from the CE-MS classifier for primary urothelial bladder cancer (AUC ¼ 0.87; 95% CI, 0.83-0.91). A three-gene methylation panel (OTX1, ONECUT2, and OSR1) detected low/intermediate risk urothelial bladder cancer with a sensitivity of 74% and specificity of 90% (43). In the current study, when investigating the subpopulation of low/intermediate-risk patients (NMIBC G 1 -G 2 ; n ¼ 26), the CE-MS-based classifier provided a sensitivity of 89% in urothelial bladder cancer detection at the preselected cut-off (AUC ¼ 0.72).…”
Section: Discussionmentioning
confidence: 99%
“…A 10-biomarker ELISA-based assay (IL8, MMP9, MMP10, SERPINA1, VEGFA, ANG, CA9, APOE, SDC1, and SERPINE1) provided an overall AUC of 0.85 (95% CI, 0.80-0.91) in discriminating urothelial bladder cancer patients from healthy and benign controls (45), slightly lower than the rates received from the CE-MS classifier for primary urothelial bladder cancer (AUC ¼ 0.87; 95% CI, 0.83-0.91). A three-gene methylation panel (OTX1, ONECUT2, and OSR1) detected low/intermediate risk urothelial bladder cancer with a sensitivity of 74% and specificity of 90% (43). In the current study, when investigating the subpopulation of low/intermediate-risk patients (NMIBC G 1 -G 2 ; n ¼ 26), the CE-MS-based classifier provided a sensitivity of 89% in urothelial bladder cancer detection at the preselected cut-off (AUC ¼ 0.72).…”
Section: Discussionmentioning
confidence: 99%
“…A number of noninvasive tests for detection of urinary non-muscle invasive B-TCC have been developed in order to overcome the low sensitivity of cytology and to reduce the number of cystoscopies, and have been reviewed by Tomasini et al (7). Following the pioneering work of Sidransky and colleagues (8), several reports have suggested the diagnostic utility of genetic and epigenetic markers (9)(10)(11). Mutations in fibroblast growth factor 3 (FGFR3) are found in a large proportion of non-muscle invasive bladder cancers (12) and may M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 therefore represent useful biomarkers for the follow-up of patients with B-TCC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that urine-based FGFR3 mutation analysis can detect recurrence, although its sensitivity may be limited if samples have few tumor cells (13)(14)(15). Recently, several studies have evaluated the sensitivity and specificity of FGFR3 mutation analysis in voided urine for detection of recurrence of superficial bladder cancer (9,(16)(17)(18). In these studies, screening for mutated FGFR3 was performed using various assays (9,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the SnapShot method proved to be highly reproducible. 27 A limitation of this study is the retrospective design. Because of the low incidence of progression in low-grade pTa disease a prospective study design is difficult to establish.…”
Section: Discussionmentioning
confidence: 98%
“…Determining DNA methylation is a highly reproducible method as we showed previously. 27 Hence these markers present a valuable tool for assessing risk of progression in patients presenting with TaG1/G2 tumors.…”
Section: Discussionmentioning
confidence: 99%